Translation Issues Analysis Committed by the 4th Year English Department Students of Unklab in Translating the Good Samaritan’s Story - Boy Lumoindong (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
A translator should be able to convey the intended meaning contained in the source language into the target one. The results of the initial observation depicted that some students in the translation class tended to translate without reading the whole text that might lead to misunderstanding of source text. This study aimed at analysing the problems faced by the student translators in translating the good Samaritan’s story from English language into Bahasa Indonesia. This study used a descriptive method. The participants were the 4th Year English Department students who took the course of Linguistic 3 as their major course. The data were taken from the Christian Biblical story in Luke 10:25-37. The data were analysed using a translation procedure. The results indicated that there are ten of problem found in the students’ translation, which are the improper use of generalization technique, improper of borrowing technique, missing the target language structure, meaning deletion, improper use of literal technique, context misunderstanding, target language interference, meaning addition, inability to find right equivalent, and source text misunderstanding.